Galangin attenuates oxidative stress-mediated apoptosis in high glucose-induced renal tubular epithelial cells through modulating renin–angiotensin system and PI3K/AKT/mTOR pathway. Issue 3 (17th May 2021) - Liao, Jie; Liu, Bo; Chen, Ke; Hu, Sheng; Liu, Zheng-Yu; Li, Yu-Xin; Yang, Zhi-Ming; Zhang, Meng; Chen, Xiong
Abstract: This study was to evaluate the regulatory network among Galangin (Gal), oxidative stress, and renin–angiotensin system (RAS) in diabetic nephropathy (DN) in vitro . A cell model of DN was set up by exposing HK-2 cells to high glucose (HG, 30 mM) for 48 h and Gal was applied at 10 μM when needed. mRNA expression was analyzed by qPCR and protein level was detected by western blot. Malondialdehyde level and superoxide dismutase activity were evaluated by commercial kits. We analyzed cell viability by CCK8 assay and apoptosis by flow cytometry. DCFH-DA staining was conveyed for reactive oxygen species detection. HG induced RAS activation, oxidative stress, while inhibited cell viability. Gal suppressed oxidative stress-mediated apoptosis of HK-2 cells under the stimulation of HG via inhibiting RAS activation. Moreover, overexpression of AT1R, a RAS gene, could restrain the mitigative effect of Gal on cell injury. Furthermore, repression of RAS induced by AT1R knockdown partially reversed HG-induced PI3K/AKT/mTOR activation and oxidative stress in HK-2 cells. Also, AKT activation could antagonize Gal's functional roles in renal cell damage. Collectively, Gal alleviates HG-induced oxidative stress injury of renal tubular epithelial cells through PI3K/AKT/mTOR signal via modulating RAS activation. This finding would help to better understand mechanism of DN development and support future studies.